Appendiceal carcinoid tumor presenting as perforated appendicitis in pediatric patients: A case series and review of the literature - Dwight Philip; Kristen Fox; Noor Kassira; Carrie Laituri; Tamar Levene (Elsevier, 2023)
Introduction: The most common location for neuroendocrine tumors (NETs) among pediatric patients is the appendix and in majority of cases, these are incidentally found during a seemingly routine appendectomy. Optimal management recommendations for incidental NETs of the appendix in the setting of perforated appendicitis have not been well defined. Cases presentation: We report three cases of adolescent females presenting with perforated appendicitis with an incidental finding of appendiceal neuroendocrine tumors (ANETs). The patients underwent initial laparoscopic appendectomy with subsequent right hemicolectomy upon histopathologic confirmation of the diagnosis of ANET. All three patients showed a grade 1 ANET on histopathological examination. All three patients remain disease-free at clinical follow-up (mean follow-up 16.3 months, range 8-32 months). Conclusion: This case series describes the treatment approaches for three adolescent female patients with perforated appendicitis secondary to ANETs, all of whom underwent subsequent right hemicolectomy. Current guidelines recommend surgical resection of these tumors to minimize complications. However, there is not consensus regarding the benefits of complete right hemicolectomy (CRH) versus appendectomy alone in this setting. Specifically, there is limited guidance for perforated appendicitis secondary to an underlying NET of the appendix. This case series and review addresses the current gap in the literature.